Implementasi Pendidikan Seksual Pada Anak Usia Dini Dalam Perspektif Islam - Utama, Abdul Alimun; Hidayati, Sri Wahyu; Sari, Indah Fitriana (Lembaga Penelitian dan Pendidikan Mandala, 2022)
This paper aims to describe the application of early childhood sex education according to an Islamic perspective and how to implement it. Seeing the rampant cases of violence and sexual abuse against early childhood, this must be a big concern for various parties, including parents, to be aware of it. Several efforts have been made, including by educating parents and children about sex education from an early age, overcoming them by limiting pornographic content on television, the internet and games, and stopping the efforts of perpetrators of violence and sexual abuse against children, namely punishing perpetrators with the heaviest punishment. From the perspective of Islamic education, sex education in children is an integral part of akidah, moral, and worship education, and has been widely discussed by Muslim scholars, based on the nash-nash of the Qur'an and Hadith. Sex education is a form of effort to provide education Sex education is a form of effort to provide education and knowledge about biological, psychological and psychosocial changes as a result of human growth and development. This education also provides an understanding of the function of sexual organs (sex) in children and instills ethical morals and religious commitments so that there is no abuse of these reproductive organs.